Industrial training report: Iskandar Regional Development Authority (IRDA) Institutional Records / Fatin Qamariah Ismail - Ismail, Fatin Qamariah (Bachelor of Information Science (Hons.) Records Management, 2015)
This project involves discovering which records of strategic project in Iskandar Regional Development Authority (IRDA) belong to which person or department. The goal is to compile blueprints records as well as strategic projects records management control and system and to know where the records are located so the records soon will be referred if anything happens to the completed project. This is because most of the projects are consist of civil construction projects such as road construction and upgrading. The data collection consists of qualitative method where several knowledge sharing sessions were held. The session was held and the content was then being produced in pictorial report to make it available to all staffs. This project entirely covered the files, records, correspondences and its content. Besides that, this project also included the process of a project starting from a concept paper to a strategic project. In developing a project, there are some of certificates and letters would be issued. The processes that are related to the archiving and indexing are important to know and locate how and where the records are kept. The daily and scheduled tasks of records and correspondences are also important to the status and problems that happen to the project. Through it all, the findings of the project came to the creation of records retention schedule. This schedule identified the types of projects and it related records either they are the active, semi-active or non-active records. Therefore, the locations of the records were known according to the retention schedule.